2021
DOI: 10.33215/sbr.v1i2.583
|View full text |Cite
|
Sign up to set email alerts
|

Does Self-Control Moderate the Relationship between Social Influence and Savings Behavior among Small Business Owners?

Abstract: This study examined whether self-control moderates the association linking social influence to saving behavior among small business owners. Using a standardized questionnaire, the study utilized a cross-sectional design to collect data from 402 micro and small business owners based in Kampala City. Process macro was used to analyze the interactive impact of self-control and social influence on saving behavior. The findings showed a significant interactive effect of self-control and social influence on saving b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Moreover, people with good self-control are able to prioritise needs over momentary desires. Self-control has a strong influence on determining saving behaviour, according to research by Trzcińska, et al [40], and other research has shown that self-control has a significant positive effect on saving behaviour Mexhuani and Ribaj [4]; Mpaata, et al [41]. Biljanovska and Palligkinis [42] also claimed that people with strict self-control can save money better.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, people with good self-control are able to prioritise needs over momentary desires. Self-control has a strong influence on determining saving behaviour, according to research by Trzcińska, et al [40], and other research has shown that self-control has a significant positive effect on saving behaviour Mexhuani and Ribaj [4]; Mpaata, et al [41]. Biljanovska and Palligkinis [42] also claimed that people with strict self-control can save money better.…”
Section: Discussionmentioning
confidence: 99%
“…Age and education have a positive and significant effect on financial literacy, with higher levels of education leading to higher levels of financial literacy (Anshika et al, 2021). Gender, length of work and income play a role in financial literacy (Mpaata et al, 2021). The level of the company's gross profit ratio was found to be the determinant that most influences financial literacy.…”
Section: Factors Influencing the Level Of Financial Literacymentioning
confidence: 92%
“…Good exercise effect can promote exercise persistence is the first hypothesis of this study. The level of selfmanagement affects the completion of people's work and study tasks [3]. This indicator ultimately affects the persistence of individual exercise behavior.…”
Section: Introductionmentioning
confidence: 99%